1955
DOI: 10.1346/ccmn.1955.0040130
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Studies on Dilute Clay Mineral Suspensions

Abstract: A technique has been developed for obtaining reproducible viscometric data on dilute clay suspensions using the recently developed capillary viscometer of Maron, Krieger and Sisko. Aging and type of mixing have important effects on the viscosity of the dispersions. Attapulgite, hectorite, and Wyoming bentonite exhibit non-Newtonian behavior at all concentrations studied. The effect of temperature on the reduced fluidifics of suspensions of the three clays is negligible. In this respect they agree with the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1957
1957
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Solution chemists have found it useful to define "apparent molar" properties for solutions of small molecules and "appar-FIG. 1. Graphs of reduced viscosity ( ( n -no)/+,no) against volume fraction of dry clay (+d) for montmorillonite (a) and kaolinite (b).…”
Section: Results and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution chemists have found it useful to define "apparent molar" properties for solutions of small molecules and "appar-FIG. 1. Graphs of reduced viscosity ( ( n -no)/+,no) against volume fraction of dry clay (+d) for montmorillonite (a) and kaolinite (b).…”
Section: Results and Calculationsmentioning
confidence: 99%
“…As background for our research we cite a few previous investigations of viscosities of dilute suspensions of clays (1)(2)(3)(4)(5)(6) and evidence for interesting and potentially important interactions of different kinds of clays with each other in dilute suspensions (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The viscometric data were obtained using either capillary viscometers or the falling head viscometer described by Wood, Granquist and Krieger (1956). Clay concentrations in the fresh water dispersions were determined gravimetrically (constant weight at ll0~…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The operation of the falling head viscometer was described in the earlier publication (Wood, Granquist and Krieger, 1956), and These viscometric data were examined by a theory of incremental viscosity and by the Schulz-Blaschke equation, and the data from these equations were used to calculate a shape factor or axial ratio from the equations of Kuhn (1933) and Simha (1940).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Even though we did not measure bed shear stress the turbidity values support the present data. In pervious studies (Wood et al 1955;Lumley 1969;Wolanski 1989), turbulence damping was shown to be the result of several factors such as the visco-elasticity of clay suspensions, the interaction and aggregation of particles (Manning and Dyer 1999), the dynamic interaction between turbulent shear strain in the flow and the deformation of aggregates (Gust and Walger 1976), and the vertical stratification of SSC (Sheng and Villaret 1989;Toorman 2000aToorman , 2000b. Li and Gust (2000) who used SSC of 8 g l À1 suggested that flocculation of clay particles is not significant in causing the observed drag reduction.…”
Section: Cloutier Et Al (2002) Who Determined In Labmentioning
confidence: 99%